2004
DOI: 10.1128/jvi.78.22.12672-12676.2004
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Modified Vaccinia Virus Ankara-Based Recombinant Vaccine against Severe Acute Respiratory Syndrome Is Associated with Enhanced Hepatitis in Ferrets

Abstract: Severe acute respiratory syndrome (SARS) caused by a newly identified coronavirus (SARS-CoV) is a serious emerging human infectious disease. In this report, we immunized ferrets (Mustela putorius furo) with recombinant modified vaccinia virus Ankara (rMVA) expressing the SARS-CoV spike (S) protein. Immunized ferrets developed a more rapid and vigorous neutralizing antibody response than control animals after challenge with SARS-CoV; however, they also exhibited strong inflammatory responses in liver tissue. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
317
5
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(341 citation statements)
references
References 19 publications
2
317
5
6
Order By: Relevance
“…There was some change in appearance of the liver in six of the 46 animals in the six groups, namely a pale or tan colour in two animals in each of the PBS, WKV and WKV+alum groups. There was no apparent evidence of enhanced liver pathology in SARS-antigen-vaccinated groups as was reported previously for the modified vaccinia virus (MVA)-vectored SARS vaccines (Czub et al, 2005;Weingartl et al, 2004). Gross pathology indicated frequent significant haemorrhage in lung and mediastinum (the area between the lungs containing the heart, trachea, oesophagus, thymus and lymph nodes), specifically the thymus (Fig.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…There was some change in appearance of the liver in six of the 46 animals in the six groups, namely a pale or tan colour in two animals in each of the PBS, WKV and WKV+alum groups. There was no apparent evidence of enhanced liver pathology in SARS-antigen-vaccinated groups as was reported previously for the modified vaccinia virus (MVA)-vectored SARS vaccines (Czub et al, 2005;Weingartl et al, 2004). Gross pathology indicated frequent significant haemorrhage in lung and mediastinum (the area between the lungs containing the heart, trachea, oesophagus, thymus and lymph nodes), specifically the thymus (Fig.…”
mentioning
confidence: 54%
“…One ferret study indicated that, upon intranasal (i.n.) administration of SARS-CoV Toronto 2 (Tor2) strain, no clinical signs were observed up to 29 days post-challenge, although viral RNA could be detected in pharyngeal swabs (Czub et al, 2005;Weingartl et al, 2004). Our preliminary studies showed clinical signs, viral replication and lung pathology in ferrets infected with SARS-CoV reflecting pathogenesis in humans ; we therefore decided to evaluate and compare our two SARS vaccine candidates (WKV and Ad expressing S and N protein) in a single trial in the ferret model (Kobinger et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, recombinant vaccinia viruses expressing different foreign viral antigens, including the HA of influenza virus, have been shown to induce protective immunity in ferrets (Jakeman et al, 1989). A recombinant MVA expressing the spike or nucleocapsid protein of severe acute respiratory syndrome (SARS) coronavirus also proved to be immunogenic (Czub et al, 2005;Weingartl et al, 2004). It is therefore unlikely that the differences in protective effectiveness in monkeys and ferrets were related to the species that was used.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reduced production of both anti-inflammatory cytokines in the mOrVV-NHis-immunized mice after SARS-CoV infection may be related to the severity of the pulmonary inflammation in these mice. Weingartl et al (47) and Czub et al (48) reported that immunization with S protein expressing-recombinant modified VV Ankara (rMVA-S) induced stronger inflammatory responses and focal necrosis in liver tissues after SARSCoV challenge than in control animals. However, the precise mechanism underlying this liver inflammation has not been clarified.…”
Section: Discussionmentioning
confidence: 99%